Integrasi Nilai Keislaman dalam Kegiatan Bermain Anak Usia Dini - Raniyah, Qaulan (AUD Cendekia: Journal of Islamic Early Childhood Education, 2025)
This study aims to describe the process of integrating Islamic values into play activities for early childhood and to identify the types of educational games used at TK Muhammadiyah Mandala. Using a qualitative method with a phenomenological approach, the research involved the principal, teachers, and parents as primary informants. The findings reveal that the integration of Islamic values occurs through three main stages: planning value-based play activities, implementing religious-themed games, and habituation and reflection on values after play. Values such as honesty (ṣidq), responsibility (amānah), cooperation (ta‘āwun), gratitude (syukr), and compassion (iḥsān) are instilled through educational games such as Islamic Mini Market, Cooperative Mosque-Building Game, Islamic Snake Game, and Tree of Goodness. Teachers play a crucial role as facilitators and moral role models, linking each play activity with Islamic teachings. Despite challenges such as limited materials and time, teacher creativity and the school’s strong religious culture support the successful integration of Islamic values. This research provides theoretical contributions to the development of Islamic education through play-based learning and practical implications for Islamic early childhood institutions in designing play activities infused with spiritual and moral values.